Influence of climate conditions on tax revenues - Mihai Mutascu (Contemporary Economics)
In this paper, we investigate the effects of climate conditions on collected tax revenues, based on a panel-model approach. The dataset includes 123 countries and covers the period 1996-2010. The main results demonstrate that climate has a significant impact on tax revenues, the assumed function being nonlinear, with a cubic ⋂ and incomplete ⋃-shape. We also find that governments situated in temperate climate zones, with low to moderate temperatures (the ‘optimal temperature’ in our investigation), can ensure a good collection of tax revenues. The study suggests that a significant increase in collected tax revenues, without a major negative reaction by taxpayers, can be easily obtained by the public authority if situated in a temperate climate zone, that is, one with moderate temperatures.